Sistem E-Commerce Menggunakan Metode Accrual Basis Dalam Pencatatan Transaksi pada Toko Terashijab - Teguh Setiadi; Hendri Rasminto; Septu Rismayani (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The Terashijab store was founded in 2018, is engaged in fashion sales, located in Dukuh Kajaan RT 01 RW 03, Purworejo Village, Ringinarum District, Kendal Regency, Central Java. In carrying out its activities, there are always promotions, sales and purchase transactions. However, the Terashijab shop does not yet have a special media as a place to increase sales and expand the sales area of ​​the shop. In recording sales and purchase transactions, manual recording is still used, namely the recording is still in the ledger which results in the resulting financial reports being unsuitable, as well as the vulnerability of data storage and difficulty in finding data so that it is not yet effective and easier in making financial reports. Based on this research, the authors designed and made the E-Commerce System application at the Hijab Store Using the Accrual Basis Method in Recording Transactions. The purpose of making this system is so that the store has a special media in increasing sales and expanding the sales area of ​​the store and for handling, processing sales data and making financial reports no longer manually and becoming more efficient and safer in storing company data.